Allergen immunotherapy in patients with autoimmune diseases: current of guidelines and emerging controversies - Dominika Ochab-Krupnik; Adam Latos; Piotr Łacwik; Maciej Kupczyk; Cezary Pałczyński (Alergologia Polska)
This review explores the use of allergen immunotherapy (AIT) in patients with comorbid autoimmune diseases, focusing on ongoing controversies and gaps in existing clinical guidelines. The aim is to unravel the complex interplay between allergic and autoimmune diseases and evaluate the safety of AIT in this specific patient population. The analysis includes historical case reports and recent observational studies, emphasizing instances where AIT was linked to exacerbations of autoimmune diseases. Notably, many of these cases involved older, less refined allergen extracts, raising questions about their applicability to modern practice. An evaluation of international guidelines reveals inconsistencies and reliance on outdated evidence. The findings highlight an urgent need for rigorous, large-scale research to establish clear, evidence-based recommendations for the safe implementation of AIT in patients with autoimmune conditions. This review emphasizes the importance of updating clinical guidelines to reflect contemporary evidence, ensuring the safe and effective application of AIT in this patient group.